Pharmacotechnological research on the development of a medicinal preparation in the form of granules for comprehensive pharmacocorrection of mastopathy - Palyvoda, Polina; Zuikina, Svitlana (Annals of Mechnikov’s Institute, 2025)
The aim of the study. To develop the composition and technology of granules based on phytoextracts for complex pharmacocorrection of mastopathy. Materials and methods. During the work, bibliosemantic, marketing, and pharmaco-technological methods of analysis were used. Results. The research materials are model samples of granules manufactured by wet granulation. The basis was a composition of phytoextracts: dry extract of clover flowers, cranberry fruits, amaranth seeds, and parsley leaves. The quality control of the proposed granule samples was carried out according to organoleptic properties (appearance, smell, taste), granule size, which was determined by sieve analysis, flowability, and moisture content, which was determined gravimetrically. Based on the results of the studies, we developed a technology for the production of granules. Quality control of model granule samples showed that the most optimal samples are those containing sodium saccharinate (№ 2, 3), sugar syrup (№ 2), corn starch (№ 2, 3, 6), 5% starch paste (№ 6), 25% PVP-K30 solution (№ 3), fructose, and aerosil (№ 6). Conclusions. Based on the results of pharmacotechnological studies, samples of the developed drug have been identified as promising for further biopharmaceutical, microbiological, and pharmacological studies. Keywords: mastopathy, granules, pharmacotechnological research, original herbal medicinal products.